On the restoration of the level of underground water after withdrawal from the layered aquifers with overflow - M. M. Burakov; V. G. Burkush; M. M. Tynbayev (Известия высших учебных заведений: Геология и разведка, 2019)
The patterns of restoration of the piezometric level of groundwater in the aquifer under test in a layered aquifer system with the overflow of water from the adjacent horizon after stopping the experimental constant-rate pumping tests, have been analyzed; the physico-mathematical model of piezometric level restoration has been formed and analyzed. It has been shown that the restoration of the level is carried out in the same way as after stopping the pumping from a pressure isolated aquifer. In other words, it has been assumed that pumping with a constant flow rate continues even after it has been stopped, and at the time of self-stopping through the well from which the pumping is performed, water is pumped into the test aquifer with the same flow rate. As a result, the disturbance flow rate becomes zero, and the groundwater level in the tested horizon is restored to an unperturbed position. In addition to this, during test filtration testing of layered systems with overflow, the groundwater flow formed during the injection, directed from the tested horizon to the adjacent one, completely "locks" the groundwater flow formed during the pumping out of the adjacent horizon to the tested one. Accordingly, the processing and interpretation of the results of tracking the recovery level should be carried out in full compliance with the existing methodological recommendations.